Pengaruh Standar Operasional Prosedur (SOP) Pengawasan, Dan Teknologi Informasi Terhadap Kinerja Karyawan Pada Unit Outbond Di PT JNE Cabang Utama Medan - Ikwan Lubis; A M Hatuaon Sihite; M. Sianturi (Jurnal of Management and Social Sciences, 2024)
JNE is the largest logistics company in Indonesia, this company is a freight forwarding company both domestically and abroad. In its business process JNE has an Outbound unit which is responsible for receiving goods from Sales Counter Official (SCO) agents and branch offices, processing, checking, packaging, and transporting goods to the appropriate destination. The purpose of this study is to determine the effect of Standard Operating Procedures (SOP), supervision, and Information Technology on Employee Performance in the operational management of the JNE Main Branch Medan Outbound unit. This research uses Descriptive Qualitative method in identifying problems. The results in this study state that SOP has a significant effect on Employee Performance because it is an important part of the smooth work process for employees, Supervision and Information Technology also have a significant effect on Employee Performance. Supervision ensures employees work in accordance with SOPs and achieve previously set work targets, and the use of Information Technology in the work process will increase the efficiency and effectiveness of employee work.